Role of phage therapy in acute gastroenteritis - Somaieh Sabzali; Setareh Pazhouhnia; Kiana Shahzamani; Peyman Adibi Sedeh (Journal of Research in Medical Sciences)
The gut ecosystem, comprising the gut microbiota and its interactions, plays a crucial role in human health and disease. This complex ecosystem involves a diverse array of microorganisms such as viruses, fungi, and bacteria, collectively known as the gut microbiota. These microorganisms contribute to various functions, including nutrient metabolism and immune modulation, thereby impacting human health. Dysbiosis, or an imbalance in the gut microbiota, has been associated with the pathogenesis of several diseases, ranging from intestinal disorders such as inflammatory bowel disease to extra-intestinal conditions such as metabolic and neurological disorders. The implications of dysbiosis in the gut ecosystem are far-reaching, affecting not only gastrointestinal health but also contributing to the development and progression of conditions such as autoimmune gastritis and gastric cancer. Furthermore, the burden of antimicrobial use and subsequent side effects, including antibiotic resistance, poses additional challenges in managing gastrointestinal diseases. In light of these complexities, investigating the role of bacteriophages as regulators of the gut ecosystem and their potential clinical applications presents a promising opportunity to tackle antibiotic resistance and fight infectious diseases.